2014
DOI: 10.1080/01443410.2014.915928
|View full text |Cite
|
Sign up to set email alerts
|

Asian students in Australia: sources of the academic self

Abstract: Students' motivation is known to be influenced by both internally referenced and externally referenced factors. Internally referenced factors include self-processes (sense of competence and affect), whereas externally referenced factors include significant others (parents, peers and teachers). Using the Facilitating Conditions Questionnaire, the relations of the internal and external factors were examined. By comparing Anglo and Asian origin students in Australia, the study aims to reveal the most prominent ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 46 publications
1
2
0
Order By: Relevance
“…As expected, relatedness was a mediator of the unique contributions of involvement from both partners, suggesting that the supports of parents and teachers are cumulative – each social partner provides support that the other cannot, and both fuel improvements in students’ engagement via this pathway (Guay, Denault, et al., 2017). Consistent with some studies of older students (e.g., Ganotice & King, 2014; Guay, Denault, et al., 2017; McInerney, 2008; Murdock & Miller, 2003; Murray, 2009; Navarro et al., 2007; Sahil & Hashim, 2011; Yeung et al., 2014), parent involvement seemed to take the lead in shaping their offspring’s sense of competence, whereas teacher support played the primary role in nurturing students’ autonomy. Taken together, study results provide a more holistic understanding of how interpersonal relationships may optimize student engagement.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…As expected, relatedness was a mediator of the unique contributions of involvement from both partners, suggesting that the supports of parents and teachers are cumulative – each social partner provides support that the other cannot, and both fuel improvements in students’ engagement via this pathway (Guay, Denault, et al., 2017). Consistent with some studies of older students (e.g., Ganotice & King, 2014; Guay, Denault, et al., 2017; McInerney, 2008; Murdock & Miller, 2003; Murray, 2009; Navarro et al., 2007; Sahil & Hashim, 2011; Yeung et al., 2014), parent involvement seemed to take the lead in shaping their offspring’s sense of competence, whereas teacher support played the primary role in nurturing students’ autonomy. Taken together, study results provide a more holistic understanding of how interpersonal relationships may optimize student engagement.…”
Section: Discussionsupporting
confidence: 83%
“…However, research with older students was mixed. Of the 10 studies examining this question during late middle or high school (Chouinard, Karsenti, & Roy, 2007; Fall & Roberts, 2012; Fan, Lindt, Arroyo‐Giner, & Wolters, 2009; Galand & Hospel, 2012; Murdock & Miller, 2003; Murray, 2009; Navarro, Flores, & Worthington, 2007; Pan, Zaff, & Donlan, 2017; Sahil & Hashim, 2011; Yeung, McInerney, & Ali, 2014), all found that parents made a unique contribution over and above the support of teachers, but only six indicated that teachers also made unique contributions.…”
Section: Introductionmentioning
confidence: 99%
“…Predictors (Time 1). Predictors were assessed using the Facilitating Conditions Questionnaire (McInerney et al, 2005;Yeung, McInerney, & Ali, 2014). This instrument measures seven dimensions: (a) school valuing (four items, ␣ ϭ .764; e.g., "Doing well at school is really important to my future"), affect toward school (three items, ␣ ϭ .656; e.g., "The subjects at school interest me"), positive influence by peers (four items, ␣ ϭ .617; e.g., "Most of my friends want to do well at school"), negative influence by peers (three items, ␣ ϭ .866; e.g., "My friends say I should leave school as soon as possible"), support from parents (four items, ␣ ϭ .786; e.g., "If I decided to go on to college or university, my father would encourage me"), negative influence by parents (four items, ␣ ϭ .902; e.g., "My mother encourages me to leave school as soon as possible"), and support from teachers (three items, ␣ ϭ .650; e.g., "I get encouragement from some of my teachers to do well at school").…”
Section: Methodsmentioning
confidence: 99%